2022
DOI: 10.5194/hess-2021-594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extreme precipitation events induce high fluxes of groundwater and associated nutrients to the coastal ocean

Abstract: Abstract. Current Submarine Groundwater Discharge (SGD) studies are commonly conducted under aquifer baseflow conditions, neglecting the influence of episodic events that can significantly increase the supply of nutrients and water. This limits our understanding of the social, biogeochemical, and ecological impacts of SGD. In this study, we evaluated the influence of an extreme precipitation event (EPE) on the magnitude of both the terrestrial and marine components of SGD. To do so, three seawater sampling cam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In turn, very few of the aquifer taxa were also detected in marine waters, suggesting that at least during the sampling period (summer), there is little microbial dispersal between aquifer and marine communities. This transport of microorganisms from the aquifer to the sea might, however, be enhanced in the wet season when groundwater discharge increases, as extreme precipitation episodes typical of spring and autumn in the study site have shown to increase SGD by 1 order of magnitude compared to baseflow conditions (Diego‐Feliu et al, 2022 ). Regardless of whether dispersal of taxa between the surface, the aquifer and the sea may shape microbial structure and functioning, our data suggest that strong selection by local conditions is the main process structuring the Argentona microbiome, at least during baseflow conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In turn, very few of the aquifer taxa were also detected in marine waters, suggesting that at least during the sampling period (summer), there is little microbial dispersal between aquifer and marine communities. This transport of microorganisms from the aquifer to the sea might, however, be enhanced in the wet season when groundwater discharge increases, as extreme precipitation episodes typical of spring and autumn in the study site have shown to increase SGD by 1 order of magnitude compared to baseflow conditions (Diego‐Feliu et al, 2022 ). Regardless of whether dispersal of taxa between the surface, the aquifer and the sea may shape microbial structure and functioning, our data suggest that strong selection by local conditions is the main process structuring the Argentona microbiome, at least during baseflow conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Other prokaryotic groups showed more gradual changes along the salinity gradient, being more prevalent in the fresher portions of the aquifer (Burkholderiales, Nitrospirota, Planctomycetota), or preferring brackish (Gamma‐ and Alphaproteobacteria) or saline sites (Bacteroidota and Campylobacterota). This means that hydrological changes, such as variations in the extent of the saline intrusion (Folch et al, 2020 ; Palacios et al, 2020 ) or the occurrence of extreme precipitation events (Diego‐Feliu et al, 2022 ), may trigger major changes in the physicochemical parameters of the subterranean estuary and thus impact communities and their associated metabolic functions. For example, increases in salinity have been associated with decreased denitrification, nitrification and anammox (anaerobic ammonium oxidation, Jiao et al, 2018 ; Santoro, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short bursts of remineralized and terrestrially derived inorganic nitrogen, via subterranean inputs, such as SGD found to increase following Hurricane Harvey in the adjacent Nueces Bay and Upper Laguna Madre (Murgulet et al, 2022), are a plausible cause for the observed trends. Other recent studies found storm events responsible for higher SGD rates and nutrient fluxes to the coastal ocean, although these occurrences were mostly driven by high precipitation rates and subsequent recharge (McKenzie et al, 2021;Diego-Feliu et al, 2022).…”
Section: Hydrologic Changes and Relationships To Nutrient Supplymentioning
confidence: 87%